2021
DOI: 10.3389/fped.2021.693348
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in an Infant With SARS-CoV-2 Infection: A Case Report and a Review of the Literature

Abstract: Coronavirus disease 2019 (COVID-19) is caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Even if predominantly considered a respiratory pathogen, it could be associated with gastrointestinal involvement, generally in mild forms. Recent reports highlight the association between SARS-CoV-2 and intussusception in infants. A case of intussusception is hereby described in a previously healthy infant in whom the diagnosis of SARS-CoV-2 was made after the analysis of bronchoalveolar lavage and intraope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Subsequently, 103 articles remained, which were analyzed in full text. In total, 34 studies met our inclusion criteria and reported SARS-CoV-2 infection in pediatric patients with ISN and were included for systematic review and meta-analysis [ 4 , 5 , 6 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The detailed characteristics of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, 103 articles remained, which were analyzed in full text. In total, 34 studies met our inclusion criteria and reported SARS-CoV-2 infection in pediatric patients with ISN and were included for systematic review and meta-analysis [ 4 , 5 , 6 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The detailed characteristics of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the included studies are shown in Table 1 . There were 28 case report [ 4 , 6 , 7 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], 5 cohort [ 20 , 34 , 42 , 43 , 44 ] and 1 case-series [ 5 ] studies. These studies were conducted in United States (n = 9), Italy (n = 4), United Kingdom (n = 3), China (n = 3), India (n = 3), Iran (n = 2), Colombia (n = 2), Jordan (n = 1), Peru (n = 1), Hungary (n = 1), Guatemala (n = 1), Spain (n = 1), Mexico (n = 1), Pakistan (n = 1), and Turkey (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical manifestations of intussusception in children are varied and non-speci c [11][12][13] . The classic triad of pediatric intussusception includes vomiting, abdominal pain, and bloody currant jelly stool/palpable abdominal mass; however, this occurs in fewer than half of affected patients 14 .…”
Section: Introductionmentioning
confidence: 99%